Liquid-gas phase behavior of polydisperse dipolar hard-sphere fluid: Extended thermodynamic perturbation theory for central force associating potential - Kalyuzhnyi, Yu.V.; Hlushak, S.; Cummings, P.T. (Condensed Matter Physics, 2012)
The liquid-gas phase diagram for polydisperse dipolar hard-sphere fluid with polydispersity in the hard-sphere size and dipolar moment is calculated using extension of the recently proposed thermodynamic perturbation theory for central force (TPT-CF) associating potential. To establish the connection with the phase behavior of ferrocolloidal dispersions it is assumed that the dipole moment is proportional to the cube of the hard-sphere diameter. We present and discuss the full phase diagram, which includes cloud and shadow curves, binodals and distribution functions of the coexisting daughter phases at different degrees of the system polydispersity. In all cases studied polydispersity increases the region of the phase instability and shifts the critical point to the higher values of the temperature and density. The larger size particles always fractionate to the liquid phase and the smaller size particles tend to move to the gas phase. At relatively high values of the system polydispersity three-phase coexistence is observed. Проведений розрахунок фазової дiаграми рiдина-газ полiдисперсної сумiшi дипольних твердих сфер з полiдисперснiстю як по розмiрах твердих сфер, так i по величинi дипольних моментiв, використовуючи узагальнення термодинамiчної теорiї збурення для систем з центральним характером асоцiативної взаємодiї. Для того, щоб встановити зв’язок з фазовою поведiнкою фероколоїдних дисперсiй, було зроблено припущення про те, що дипольний момент частинки є пропорцiйний до кубу її дiаметра. Ми представили та обговорили повну фазову дiаграму, яка включає кривi ‘хмари’ та ‘тiнi’, бiнодалi та функцiї розподiлу спiвiснуючих дочiрнiх фаз при рiзних значеннях полiдисперсностi системи. У всiх випадках, якi дослiджувалися, полiдисперснiсть збiльшує область фазової нестабiльностi та змiщує критичну точку в область вищих температур та густин. Частинки бiльшого розмiру завжди фракцiонують у рiдинну фазу, а частинки меншого розмiру вiддають перевагу газовiй фазi. У випадку вiдносно високого значення полiдисперсностi системи було вiдмiчено наявнiсть спiвiснування трьох фаз.